Mineral reinforced PC / ABS (polycarbonate / acrylonitrile butadiene styrene) resin composition with thermal stability and preparation method of mineral reinforced PC / ABS resin composition
By combining low-alkaline talc powder and metal ion complexing agent, the thermal stability and silver wire defects of mineral-enhanced PC/ABS resin materials are solved, which significantly improves the thermal stability and mechanical properties of the material, and broadens the Its application scope.
Patent Information
- Application Number
- CN202411589430.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-01-17
AI Technical Summary
The existing mineral-reinforced PC/ABS resin materials are prone to insufficient thermal stability and defects in silver wire during injection molding during processing, which limits their use in applications with high appearance requirements.
The method of combining low-alkaline talc powder and metal ion complexing agent is adopted to weaken the alkalinity of talc powder through acid regulators, and the trace metal ions in talc powder are adsorbed through metal ion complexing agents to improve the thermal stability of the material. And it is melted, homogenized, stripped, cooled and pelletized in a twin-screw extruder.
It significantly improves the thermal stability of mineral-enhanced PC/ABS resin, improves silver wire defects on injection molded surfaces, expands the application field of materials, and maintains excellent mechanical properties.
Smart Images

Figure BDA0005125175160000021 
Figure BDA0005125175160000041 
Figure BDA0005125175160000051
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials and relates to a mineral-reinforced resin composition, in particular to a mineral-reinforced PC / ABS resin composition with thermal stability and a preparation method thereof. Background Art
[0002] Polycarbonate resin (PC) is well-known for its many superior properties, including excellent flame retardancy, high heat resistance, high impact resistance, high transparency and excellent dimensional stability. Various PC modified materials are emerging in an endless stream, especially PC / ABS resin, which is being researched and applied more and more widely and can be widely used in home appliances, automobiles, power tools, new energy, OA, security equipment and other fields; however, when PC / ABS resin is used to manufacture thin-walled large parts, it often faces the problems of easy deformation and insufficient modulus.
[0003] Mineral reinforcement system is a common method to improve the dimensional stability and modulus of PC / ABS resin. Among them, glass fiber reinforcement system can provide excellent reinforcement effect, but its surface is prone to obvious floating fiber phenomenon, which often affects the scope of application. In contrast, although the talc reinforcement system is slightly inferior to the glass fiber system in reinforcement effect, it can provide a better appearance, so it is more suitable for manufacturing parts with high requirements for appearance quality.
[0004] As an inorganic mineral, talc can enhance the dimensional stability and improve the modulus of the PC / ABS system, but it has natural alkalinity and trace amounts of metal ions. Since PC is extremely sensitive to alkalinity and metal ions, these characteristics can easily lead to material degradation during processing, thus affecting thermal stability. Especially when producing large parts or using point-gate molds for injection molding, talc-reinforced PC / ABS resin materials are prone to surface defects such as silver streaks, which limits their use in applications that require high appearance. Summary of the invention
[0005] The purpose of the present invention is to provide a mineral-reinforced PC / ABS resin composition with thermal stability and a preparation method thereof in order to overcome the defects of the above-mentioned prior art. The resin composition not only has excellent mechanical properties, but also has excellent thermal stability, greatly improves the defects of silver wire on the injection molding surface, and is very suitable for application in the fields of automobiles, office equipment, electronic and electrical equipment, home appliances, security equipment, etc.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] The present invention provides a mineral-reinforced PC / ABS resin composition with thermal stability, which comprises the following components in parts by weight:
[0008]
[0009] Furthermore, the PC resin has a melt index of 10 to 20 g / 10 min at 300° C. and a load of 1.2 kg.
[0010] Furthermore, the melt index of the ABS resin at 200° C. and a load of 10 kg is 10 to 30 g / 10 min.
[0011] Furthermore, the talcum powder is low-alkalinity talcum powder with a pH value of 7.0 to 9.0 and a particle size of 1 μm to 5 μm.
[0012] Furthermore, the toughening agent is a methyl methacrylate-butadiene-styrene copolymer (MBS) with a core-shell structure, a particle size of 150nm to 250nm, and a polybutadiene content of the rubber component of 55% to 65%.
[0013] Furthermore, the acidic regulator is fumed silica with a particle size of 150nm to 350nm and a specific surface area of 150m 2 / g~400m 2 / g, pH value is 3.5~4.5.
[0014] Furthermore, the metal ion complexing agent is an aminocarboxylic acid chelating agent or a hydroxycarboxylate chelating agent, selected from at least one of ethylenediaminetetraacetic acid, aminotriacetic acid, diethylenetriaminepentaacetic acid, sodium gluconate, sodium tartrate, and sodium citrate.
[0015] Furthermore, the auxiliary agent is selected from at least one of silane coupling agent, titanate coupling agent, hindered phenol antioxidant, phosphite antioxidant, ethylene distearate, amine, polyethylene wax, pentaerythritol stearate (PETS), magnesium stearate, calcium stearate, and benzotriazole UV absorber.
[0016] The present invention also provides a method for preparing any of the above-mentioned mineral-reinforced PC / ABS resin compositions having thermal stability, comprising the following steps:
[0017] PC resin, ABS resin, talcum powder, toughening agent, acid regulator, metal ion complexing agent and additives are mixed and stirred, and after being evenly stirred, they are sent to a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted, homogenized, drawn, cooled and pelletized to obtain a mineral-reinforced PC / ABS resin composition with thermal stability.
[0018] Furthermore, the twin-screw extruder has a screw aspect ratio of 30 to 50, preferably 40, an extrusion temperature of 250° C. to 260° C., and a screw speed of 300 to 500 rpm, preferably 400 rpm.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] (1) The present invention provides a thermally stable mineral-reinforced PC / ABS resin composition and a preparation method thereof. The alkalinity of talc is weakened by an acidic regulator, and a metal ion complexing agent is used to adsorb trace metal ions brought by the talc, thereby greatly improving the thermal stability of the talc-reinforced PC / ABS system, significantly improving the silver threads on the injection molding surface, and maintaining excellent mechanical properties.
[0021] (2) The present invention provides a thermally stable mineral-reinforced PC / ABS resin composition and a preparation method thereof, wherein the preparation method focuses on reducing the alkalinity of talcum powder and chelating the trace metal ions brought by the talcum powder. Through this dual improvement strategy, the present invention effectively solves the problem of insufficient thermal stability of mineral-reinforced PC / ABS resin in the prior art and the easy generation of silver wire during injection molding. This improvement significantly improves the thermal stability of the talcum powder-reinforced PC / ABS system and significantly improves the injection molding silver wire phenomenon, thereby greatly expanding the application field of mineral-reinforced PC / ABS materials; the mineral-reinforced PC / ABS resin composition prepared based on the above-mentioned preparation method not only has excellent mechanical properties, but also has excellent thermal stability, greatly improves the defects of silver wire on the injection molding surface, and is very suitable for use in the fields of automobiles, office equipment, electronic and electrical, home appliances, security equipment, etc. DETAILED DESCRIPTION
[0022] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiment.
[0023] The present invention provides a mineral-reinforced PC / ABS resin composition with thermal stability, which comprises the following components in parts by weight:
[0024]
[0025] The PC resin has a melt index of 10 to 20 g / 10 min at 300° C. and a load of 1.2 kg.
[0026] The ABS resin has a melt index of 10 to 30 g / 10 min at 200° C. and a load of 10 kg.
[0027] Wherein, the talcum powder is low-alkalinity talcum powder with a pH value of 7.0-9.0 and a particle size of 1 μm-5 μm.
[0028] The toughening agent is a methyl methacrylate-butadiene-styrene copolymer (MBS) with a core-shell structure, the particle size is 150nm-250nm, and the polybutadiene content of the rubber component is 55%-65%.
[0029] The acidic regulator is fumed silica with a particle size of 150 nm to 350 nm and a specific surface area of 150 m 2 / g~400m 2 / g, pH value is 3.5~4.5.
[0030] Wherein, the metal ion complexing agent is an aminocarboxylic acid chelating agent or a hydroxycarboxylate chelating agent, selected from at least one of ethylenediaminetetraacetic acid, aminotriacetic acid, diethylenetriaminepentaacetic acid, sodium gluconate, sodium tartrate, and sodium citrate.
[0031] The auxiliary agent is selected from at least one of silane coupling agent, titanate coupling agent, hindered phenol antioxidant, phosphite antioxidant, ethylene distearate, amine, polyethylene wax, pentaerythritol stearate, magnesium stearate, calcium stearate, and benzotriazole UV absorber.
[0032] The above-mentioned mineral-reinforced PC / ABS resin composition with thermal stability is prepared by the following method:
[0033] PC resin, ABS resin, talcum powder, toughening agent, acidic regulator, metal ion complexing agent and auxiliary agent are mixed and stirred, and after being uniformly stirred, they are sent to a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted, homogenized, drawn, cooled and pelletized to obtain a mineral-reinforced PC / ABS resin composition with thermal stability. The twin-screw extruder has a screw aspect ratio of 30 to 50, preferably 40, an extrusion temperature of 250° C. to 260° C., and a screw speed of 300 to 500 rpm, preferably 400 rpm.
[0034] The raw materials and equipment used in the present invention are all conventional raw materials and equipment in the art. In the following embodiments, raw materials or processing techniques, unless otherwise specified, are all conventional commercially available raw materials or conventional processing techniques in the art.
[0035] PC resin S2000UR used in the present invention was purchased from Shanghai Mitsubishi, with a melt index of 10 g / 10 min (300° C., 1.2 kg); ABS resin PA747 was purchased from Chi Mei, with a melt index of 13 g / 10 min (220° C., 10 kg); talcum powder 3CA was purchased from Yiruishi; toughening agent MBS EM500 was purchased from LG Chemical; fumed silica M-5 was purchased from Cabot; sodium citrate, analytical grade, commercially available; sodium gluconate, analytical grade, commercially available; antioxidant Irganox B900 was purchased from CIBA Fine Chemicals; lubricant pentaerythritol stearate (PETS), commercially available.
[0036] Example 1
[0037] This embodiment provides a mineral-reinforced PC / ABS resin composition with thermal stability, which comprises the following components in parts by weight:
[0038]
[0039] The PC resin S2000UR, ABS resin PA747, talcum powder 3CA, toughening agent MBS EM500, acidic regulator phase silica M-5, metal ion complexing agent sodium citrate, antioxidant Irganox B900 additive and lubricant PETS additive are stirred and fully mixed in a high-speed mixer, and then sent to a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted and compounded, and then extruded, drawn, cooled and pelletized to obtain a mineral-reinforced PC / ABS resin composition with thermal stability. The twin-screw extruder has a screw length-to-diameter ratio of 40, an extrusion temperature of 255° C., and a screw speed of 400 rpm.
[0040] Example 2
[0041] This embodiment provides a mineral-reinforced PC / ABS resin composition with thermal stability, which comprises the following components in parts by weight:
[0042]
[0043] The PC resin S2000UR, ABS resin PA747, talcum powder 3CA, toughening agent MBS EM500, acidic regulator phase silica M-5, metal ion complexing agent sodium citrate, antioxidant Irganox B900 additive and lubricant PETS additive are stirred and fully mixed in a high-speed mixer, and then sent to a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted and compounded, and then extruded, drawn, cooled and pelletized to obtain a mineral-reinforced PC / ABS resin composition with thermal stability. The twin-screw extruder has a screw length-to-diameter ratio of 40, an extrusion temperature of 255° C., and a screw speed of 400 rpm.
[0044] Example 3
[0045] This embodiment provides a mineral-reinforced PC / ABS resin composition with thermal stability, which comprises the following components in parts by weight:
[0046]
[0047] The PC resin S2000UR, ABS resin PA747, talcum powder 3CA, toughening agent MBS EM500, acidic regulator phase silica M-5, metal ion complexing agent sodium citrate, antioxidant Irganox B900 additive and lubricant PETS additive are stirred and fully mixed in a high-speed mixer, and then sent to a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted and compounded, and then extruded, drawn, cooled and pelletized to obtain a mineral-reinforced PC / ABS resin composition with thermal stability. The twin-screw extruder has a screw length-to-diameter ratio of 40, an extrusion temperature of 255° C., and a screw speed of 400 rpm.
[0048] Example 4
[0049] This embodiment provides a mineral-reinforced PC / ABS resin composition with thermal stability, which comprises the following components in parts by weight:
[0050]
[0051] The PC resin S2000UR, ABS resin PA747, talcum powder 3CA, toughening agent MBS EM500, acidic regulator phase silica M-5, metal ion complexing agent sodium gluconate, antioxidant Irganox B900 auxiliary agent and lubricant PETS auxiliary agent are stirred and fully mixed in a high-speed mixer, and then sent to a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted and compounded, and then extruded, drawn, cooled and pelletized to obtain a mineral-reinforced PC / ABS resin composition with thermal stability. The twin-screw extruder has a screw length-to-diameter ratio of 40, an extrusion temperature of 255° C., and a screw speed of 400 rpm.
[0052] Example 5
[0053] This embodiment provides a mineral-reinforced PC / ABS resin composition with thermal stability, which comprises the following components in parts by weight:
[0054]
[0055]
[0056] The PC resin S2000UR, ABS resin PA747, talcum powder 3CA, toughening agent MBS EM500, acidic regulator phase silica M-5, metal ion complexing agent sodium citrate, antioxidant Irganox B900 additive and lubricant PETS additive are stirred and fully mixed in a high-speed mixer, and then sent to a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted and compounded, and then extruded, drawn, cooled and pelletized to obtain a mineral-reinforced PC / ABS resin composition with thermal stability. The twin-screw extruder has a screw length-to-diameter ratio of 40, an extrusion temperature of 255° C., and a screw speed of 400 rpm.
[0057] Example 6
[0058] This embodiment provides a mineral-reinforced PC / ABS resin composition with thermal stability, which comprises the following components in parts by weight:
[0059]
[0060] The PC resin S2000UR, ABS resin PA747, talcum powder 3CA, toughening agent MBS EM500, acidic regulator phase silica M-5, metal ion complexing agent sodium citrate, antioxidant Irganox B900 additive and lubricant PETS additive are stirred and fully mixed in a high-speed mixer, and then sent to a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted and compounded, and then extruded, drawn, cooled and pelletized to obtain a mineral-reinforced PC / ABS resin composition with thermal stability. The twin-screw extruder has a screw length-to-diameter ratio of 40, an extrusion temperature of 255° C., and a screw speed of 400 rpm.
[0061] Example 7
[0062] This embodiment provides a mineral-reinforced PC / ABS resin composition with thermal stability, which comprises the following components in parts by weight:
[0063]
[0064] The PC resin S2000UR, ABS resin PA747, talcum powder 3CA, toughening agent MBS EM500, acidic regulator phase silica M-5, metal ion complexing agent sodium citrate, antioxidant Irganox B900 additive and lubricant PETS additive are stirred and fully mixed in a high-speed mixer, and then sent to a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted and compounded, and then extruded, drawn, cooled and pelletized to obtain a mineral-reinforced PC / ABS resin composition with thermal stability. The twin-screw extruder has a screw length-to-diameter ratio of 40, an extrusion temperature of 255° C., and a screw speed of 400 rpm.
[0065] Comparative Example 1
[0066] This comparative example provides a mineral-reinforced PC / ABS resin composition, which comprises the following components in parts by weight:
[0067]
[0068]
[0069] The PC resin S2000UR, ABS resin PA747, talcum powder 3CA, toughening agent MBS EM500, antioxidant Irganox B900 and lubricant PETS are stirred and mixed in a high-speed mixer, and then sent to a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted and compounded, and then extruded, drawn, cooled and pelletized to obtain a mineral-reinforced PC / ABS resin composition. The twin-screw extruder has a screw length-to-diameter ratio of 40, an extrusion temperature of 255° C., and a screw speed of 400 rpm.
[0070] Comparative Example 2
[0071] This comparative example provides a mineral-reinforced PC / ABS resin composition, which comprises the following components in parts by weight:
[0072]
[0073] The PC resin S2000UR, ABS resin PA747, talcum powder 3CA, toughening agent MBS EM500, antioxidant Irganox B900 and lubricant PETS are stirred and mixed in a high-speed mixer, and then sent to a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted and compounded, and then extruded, drawn, cooled and pelletized to obtain a mineral-reinforced PC / ABS resin composition. The twin-screw extruder has a screw length-to-diameter ratio of 40, an extrusion temperature of 255° C., and a screw speed of 400 rpm.
[0074] Comparative Example 3
[0075] This comparative example provides a mineral-reinforced PC / ABS resin composition, which comprises the following components in parts by weight:
[0076]
[0077] The PC resin S2000UR, ABS resin PA747, talcum powder 3CA, toughening agent MBS EM500, metal ion complexing agent sodium citrate, antioxidant Irganox B900 additive and lubricant PETS additive are stirred and fully mixed in a high-speed mixer, and then sent to a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted and compounded, and then extruded, drawn, cooled and pelletized to obtain a mineral-reinforced PC / ABS resin composition. The twin-screw extruder has a screw length-to-diameter ratio of 40, an extrusion temperature of 255° C., and a screw speed of 400 rpm.
[0078] Comparative Example 4
[0079] This comparative example provides a mineral-reinforced PC / ABS resin composition, which comprises the following components in parts by weight:
[0080]
[0081] The PC resin S2000UR, ABS resin PA747, talcum powder 3CA, toughening agent MBS EM500, acidic regulator fumed silica M-5, antioxidant Irganox B900 additive and lubricant PETS additive are stirred and fully mixed in a high-speed mixer, and then sent to a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted and compounded, and then extruded, drawn, cooled and pelletized to obtain a mineral-reinforced PC / ABS resin composition. The twin-screw extruder has a screw length-to-diameter ratio of 40, an extrusion temperature of 255° C., and a screw speed of 400 rpm.
[0082] Comparative Example 5
[0083] This comparative example provides a mineral-reinforced PC / ABS resin composition, which comprises the following components in parts by weight:
[0084]
[0085] The PC resin S2000UR, ABS resin PA747, talcum powder 3CA, toughening agent MBS EM500, metal ion complexing agent sodium citrate, antioxidant Irganox B900 additive and lubricant PETS additive are stirred and fully mixed in a high-speed mixer, and then sent to a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted and compounded, and then extruded, drawn, cooled and pelletized to obtain a mineral-reinforced PC / ABS resin composition. The twin-screw extruder has a screw length-to-diameter ratio of 40, an extrusion temperature of 255° C., and a screw speed of 400 rpm.
[0086] Comparative Example 6
[0087] This comparative example provides a mineral-reinforced PC / ABS resin composition, which comprises the following components in parts by weight:
[0088]
[0089]
[0090] The PC resin S2000UR, ABS resin PA747, talcum powder 3CA, toughening agent MBS EM500, metal ion complexing agent sodium gluconate, antioxidant Irganox B900 additive and lubricant PETS additive are stirred and fully mixed in a high-speed mixer, and then sent to a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted and compounded, and then extruded, drawn, cooled and pelletized to obtain a mineral-reinforced PC / ABS resin composition. The twin-screw extruder has a screw length-to-diameter ratio of 40, an extrusion temperature of 255° C., and a screw speed of 400 rpm.
[0091] Comparative Example 7
[0092] This comparative example provides a mineral-reinforced PC / ABS resin composition, which comprises the following components in parts by weight:
[0093]
[0094] The PC resin S2000UR, ABS resin PA747, talcum powder 3CA, toughening agent MBS EM500, acidic regulator fumed silica M-5, antioxidant Irganox B900 additive and lubricant PETS additive are stirred and fully mixed in a high-speed mixer, and then sent to a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted and compounded, and then extruded, drawn, cooled and pelletized to obtain a mineral-reinforced PC / ABS resin composition. The twin-screw extruder has a screw length-to-diameter ratio of 40, an extrusion temperature of 255° C., and a screw speed of 400 rpm.
[0095] Comparative Example 8
[0096] This comparative example provides a mineral-reinforced PC / ABS resin composition, which comprises the following components in parts by weight:
[0097]
[0098] The PC resin S2000UR, ABS resin PA747, talcum powder 3CA, toughening agent MBS EM500, antioxidant Irganox B900 and lubricant PETS are stirred and mixed in a high-speed mixer, and then sent to a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted and compounded, and then extruded, drawn, cooled and pelletized to obtain a mineral-reinforced PC / ABS resin composition. The twin-screw extruder has a screw length-to-diameter ratio of 40, an extrusion temperature of 255° C., and a screw speed of 400 rpm.
[0099] Performance testing (tensile strength, melt index, impact strength, heat retention injection molding)
[0100] The performance tests of the above Examples 1-7 and Comparative Examples 1-8 are as follows:
[0101] The tensile strength test was carried out according to ASTM D638 standard, and the test speed was 50 mm / min.
[0102] The melt index test was carried out according to ASTM D1238 standard, with a load of 5 kg and a test temperature of 260°C.
[0103] The notched impact strength (3.2 mm) test was carried out according to ASTM D256.
[0104] Thermal stability test: The injection molding machine was used for hot dwell injection molding, the injection temperature was 270°C, and the dwell time was 5min and 10min respectively, and the silver wire situation on the surface of the sample was visually inspected.
[0105] The components, contents (by weight) and properties of the above-mentioned Examples 1-7 and Comparative Examples 1-8 are shown in Table 1.
[0106] Table 1 Components, contents (weight) and properties in Examples 1-7 and Comparative Examples 1-8
[0107]
[0108] It can be seen from Table 1 Comparative Example 3, Table 1 Example 1 and Table 1 Comparative Examples 5-6 that when the metal ion complexing agent sodium citrate or sodium gluconate is used alone without using the fumed silica acidity regulator, there is a problem of poor thermal stability, and the surface silver wire problem occurs during injection molding at 270°C for 10 minutes;
[0109] It can be seen from Example 2 and Comparative Example 4 in Table 1, Example 1 in Table 1 and Comparative Example 7 in Table 1 that when the fumed silica acidity regulator is used alone without using the metal ion complexing agent sodium citrate or sodium gluconate, there is a problem of poor thermal stability, and the surface silver wire problem occurs during injection molding at 270°C for 10 minutes;
[0110] It can be seen from Table 1 Comparative Examples 1-2, Table 1 Example 1 and Table 1 Comparative Example 8 that when the fumed silica acidity regulator and the metal ion complexing agent sodium citrate or sodium gluconate are not added, the problem of poor thermal stability also exists, and the surface silver wire problem occurs during injection molding at 270°C for 10 minutes;
[0111] It can be seen from the embodiments and comparative examples in Table 1 that the present invention adopts fumed silica acidity regulator and metal ion complexing agent (sodium citrate metal ion complexing agent or sodium gluconate metal ion complexing agent) to significantly improve the thermal stability of talc-reinforced PC / ABS system. When injection molding is carried out at 270°C for 5 min and 10 min, there is no problem of surface silver wire, and the system also has excellent mechanical properties.
[0112] In summary, the thermally stable mineral-reinforced PC / ABS resin composition provided by the present invention reduces the alkalinity of talc and complexes the trace metal ions brought by the talc. Through this dual improvement effect, the thermal stability of the talc-reinforced PC / ABS system is greatly improved, the surface silver wire problem generated during the injection molding process can be greatly improved, and the application range of the mineral-reinforced PC / ABS material is greatly broadened.
[0113] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A mineral-reinforced PC / ABS resin composition having thermal stability, characterized in that: By weight, it includes the following components:
2. A thermally stable mineral-reinforced PC / ABS resin composition according to claim 1, characterized in that: The PC resin has a melt index of 10 to 20 g / 10 min at 300° C. and a load of 1.2 kg.
3. The mineral-reinforced PC / ABS resin composition with thermal stability according to claim 1, characterized in that: The ABS resin has a melt index of 10 to 30 g / 10 min at 200° C. and a load of 10 kg.
4. The mineral-reinforced PC / ABS resin composition with thermal stability according to claim 1, characterized in that: The talcum powder is low-alkalinity talcum powder with a pH value of 7.0-9.0 and a particle size of 1 μm-5 μm.
5. The mineral-reinforced PC / ABS resin composition with thermal stability according to claim 1, characterized in that: The toughening agent is methyl methacrylate-butadiene-styrene copolymer (MBS) with a core-shell structure, with a particle size of 150nm-250nm, and a polybutadiene content of the rubber component of 55%-65%.
6. The mineral-reinforced PC / ABS resin composition with thermal stability according to claim 1, characterized in that: The acidic regulator is fumed silica with a particle size of 150nm to 350nm and a specific surface area of 150m 2 / g~400m 2 / g, pH value is 3.5~4.
5.
7. The thermally stable mineral-reinforced PC / ABS resin composition according to claim 1, characterized in that: The metal ion complexing agent is an aminocarboxylic acid chelating agent or a hydroxycarboxylate chelating agent, and is selected from at least one of ethylenediaminetetraacetic acid, aminotriacetic acid, diethylenetriaminepentaacetic acid, sodium gluconate, sodium tartrate, and sodium citrate.
8. The mineral-reinforced PC / ABS resin composition with thermal stability according to claim 1, characterized in that: The auxiliary agent is selected from at least one of silane coupling agent, titanate coupling agent, hindered phenol antioxidant, phosphite antioxidant, ethylene distearate, amine, polyethylene wax, pentaerythritol stearate, magnesium stearate, calcium stearate, and benzotriazole UV absorber.
9. A method for preparing a mineral-reinforced PC / ABS resin composition having thermal stability as claimed in any one of claims 1 to 8, characterized in that: The steps include: PC resin, ABS resin, talcum powder, toughening agent, acid regulator, metal ion complexing agent and additives are mixed and stirred, and after being evenly stirred, they are sent to a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted, homogenized, drawn, cooled and pelletized to obtain a mineral-reinforced PC / ABS resin composition with thermal stability.
10. The method for preparing a mineral-reinforced PC / ABS resin composition with thermal stability according to claim 9, characterized in that: The screw length-diameter ratio of the twin-screw extruder is 30-50, the extrusion temperature is 250° C.-260° C., and the screw speed is 300-500 rpm.
Citation Information
Cited By
PC / pet alloy material, preparation method therefor, and use thereof
WO2026208827A1